Made-up minds : a constructivist approach to artificial intelligence - Drescher, Gary L.; IEEE Xplore (Online Service); MIT Press (Cambridge, Massachusetts : MIT Press, 1991)
Made-Up Minds addresses fundamental questions of learning and concept invention by means of an innovative computer program that is based on the cognitive-developmental theory of psychologist Jean Piaget. Drescher uses Piaget's theory as a source of inspiration for the design of an artificial cognitive system called the schema mechanism, and then uses the system to elaborate and test Piaget's theory. The approach is original enough that readers need not have extensive knowledge of artificial intelligence, and a chapter summarizing Piaget assists readers who lack a background in developmental psychology. The schema mechanism learns from its experiences, expressing discoveries in its existing representational vocabulary, and extending that vocabulary with new concepts. A novel empirical learning technique, marginal attribution, can find results of an action that are obscure because each occurs rarely in general, although reliably under certain conditions. Drescher shows that several early milestones in the Piagetian infant's invention of the concept of persistent object can be replicated by the schema mechanism.
Outgrowth of the author's thesis (Ph. D.)--Massachusetts Institute of Technology.
Includes bibliographical references (p. [215]-218) and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/23/2015.
Keywords: Piaget, Jean, -- 1896-1980.; Concept learning; Human information processing; Schematism (Philosophy); Artificial intelligence; Electronic books